Optimization of high-speed train timetable based on regenerative braking energy utilization - GE Xin; ZHANG Yuzhao; HUANG Zhipeng (Shenzhen Daxue xuebao. Ligong ban)
Multiple units train generates a large amount of regenerative braking energy during braking, which can be used by traction trains in the same power supply zone. Making full use of this regenerative energy is of great practical significance for green transportation on high-speed rail. In this study, we construct an integer programming model with the goal of maximizing the utilization of the regenerative braking energy in the timetable. We solve the model by using the Gurobi solver under the consideration of the constraints such as the safe running interval of multiple trains and the connection of electric multiple unit trains (EMUs). Finally, we test the validity of the model by an example. The results show that the optimized train schedule has 49.3% utilization rate of regenerative braking energy, saving 14 967.622 kW‧h of traction energy consumption, indicating significant energy-saving effects. Through the comparative analysis with the simulated annealing algorithm, we conclude that the Gurobi solver is better in terms of accuracy and efficiency. The proposed method can provide a reference for operating departments to formulate the energy-saving timetables.